LUTTE CONTRE LES DISCRIMINATIONS ET GESTION DE LA DIVERSITE DES GENRES AU MAROC : REFLEXIONS SUR DES ACTIONS A ENTREPRENDRE POUR LA PERFORMANCE DES ENTREPRISES - Yasmina BENNIS BENNANI; Adil CHERKAOUI (Revue Economie, Gestion et Société, 2020)
The share of women in working population in Morocco has reduced since these last ten years, from 30% to 24%. It’s a lost for the economy of our country, above when we see the evolution of official laws enhancing equality between men and women, and the necessity to maintain our country with a sustainable economic growth. The strategy of development of Morocco integrate (societal) development which include sustainable development et gender approach. Firms must do their own introspection for attract and hold back women’s talents by gender mainstreaming.